PERWUJUDAN SIKAP TOLERANSI PADA SISWA KELAS II SMA NEGERI 1 PULAU MOROTAI - Subhan Hayun (EDUKASI, 2016)
In nation buliding, the process of raising and maintaining awarenes of the attitude of tolerance is a very fundamental in order to preserve national identity and spirit of tolerance among the studens SMAN 1 Pulau Morotai has been done by way of providing edukation history of planting Pancasila values to studens, so the attitude of tolerance that have enough studens to rese. Tolerance SMAN 1 students of Morotai in the category average is quite high. Estabilisme of tolerance on students, influenced by student interest in studying the history and the ability of students to clarify the volue of history. Interest in studying the history and values clarification skills Pancasila together, able to explain the changing attitudes of tolerance among the students SMA Negeri 1 Pulau Morotai. This type of research is a qualitative aproach deskriptipf research, data collection menthods through obsefasi, documentation, and wawancara. Tujuan this researchis to describe the attitude of tolerance manifestation of clas II SMA Negeri 1 Pulau Morotai.Based on their analysis of the data that the efforts of teachers in creating a class II student tolerance SMAN 1 Pulau Morotai is to provide learning facilities completed and remedial programs, while supporting factor is the provision of learning facilities such as library (tex books) have been carried out and the quality of teahers continue to be improved. Keywords: students’ tolerance attitude